Signaling Theory: State of the Theory and Its Future - Connelly, Brian L.; Certo, S. Trevis; Reutzel, Christopher R.; DesJardine, Mark R.; Zhou, Yi Shi (Journal of Management, 2025)
Signaling theory is about decision-making and communication. It describes scenarios where signalers send observable signals that carry credible information about unobservable qualities. When decision-makers have incomplete or imperfect information, signals can help them make better decisions. The power of a signal, though, lies in its cost, with the best signals being highly costly for low-quality signalers and less costly for high-quality signalers. Given the centrality of these ideas in the organizational sciences, we examine management studies that use signaling theory to help explain phenomena that occur within and among organizations. Our review draws attention to how signaling theorists have introduced important complexities to the signaling process, uncovered theoretical boundary conditions of signaling, described new actors within signaling systems, and demonstrated novel ways to apply signaling theory to understand behavior in an array of research contexts involving a wide range of organizational stakeholders. We also offer ideas about how scholars can account for costs when they apply the theory, extend the theory in more organizational settings, and create abstract extensions of the theory’s major concepts. Our intent is to provide researchers with a panoramic perspective on the state of signaling theory and inspire further development so that we can collectively advance signaling theory as much in the next decade as it has advanced in the last.